Foreign players and football supporters : the Old Firm, Arsenal, Paris Saint-Germain - Ranc, David (Manchester University Press ; Distributed in the U.S. exclusively by Palgrave Macmillan, 2012)
'Mercenaries', 'cheats', destroying the soul of (English) football', 'destroying the link between football clubs and their supporters': foreign football players have been accused of being at the origin of all the ills of contemporary football. How true is this? Divided into three case studies on the Old Firm, Arsenal and Paris Saint Germain, this book looks at supporters' reactions to the increase in the number of foreigners playing for their clubs.